Kerala Economy at the Crossroads? - K\P Kannan (Economic and Political Weekly September 1-8, 1990, 1990)
Implicit in the development experience of Kerala is the question of the capability of low income agrarian societies to achieve high quality of living levels. This issue is crucial for two reasons. One is related to the sustainability of the kind of social development achieved and the other is the imperative of a more all-round pattern of development.The set of articles presented in this and the following issue are, therefore, addressed to the crucial question of the economic performance of Kerala against the background of its achievements in the social sphere. While a fair amount of literature exists on Kerala's achievements in the sphere of social development, studies on the performance of the directly productive sectors of the economy are still inadequate. These papers constitute an effort to fill a part of this gap in the state of knowledge on the Kerala economy. In this paper an attempt is made to provide, in a preliminary fashion, an analytical framework within which the stagnation/slow growth of the directly productive sectors of Kerala's economy can be understood. Section II of the paper presents a picture of the nature of economic growth in Kerala in terms of the three broad sectors and the following section looks at the continuing constraints on economic growth and development with the focus on the disjunction between labour productivity and product wages, caused probably by the impact of the sudden increase in the flow of remittances since the mid-seventies, which might also explain the relatively fast growth of the tertiary sector